2001
DOI: 10.1007/s004210100383
|View full text |Cite
|
Sign up to set email alerts
|

REM sleep and catecholamine excretion: a study in elite athletes

Abstract: We investigated the potential influence of catecholamines on sleep architecture in endurance-trained athletes. The hypothesis was that endogenous levels of aminergic neurotransmitters influence sleep architecture. Thirteen well-trained male street cyclists (all members of the German national amateur team, mean age 23.9 years, mean body mass index 21.9 kg/m2) completed the protocol. Each subject was studied during training after a race competition (C) and later in a recovery/rest period (R) with no training and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 17 publications
6
35
2
1
Order By: Relevance
“…There is some evidence that athletes’ sleep is impaired by high training loads,29 competition exercise24 and the anticipation of competition 30. In this study, however, match competition did not affect the Australians’ sleep, and it improved some aspects of the Bolivians’ sleep.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…There is some evidence that athletes’ sleep is impaired by high training loads,29 competition exercise24 and the anticipation of competition 30. In this study, however, match competition did not affect the Australians’ sleep, and it improved some aspects of the Bolivians’ sleep.…”
Section: Discussioncontrasting
confidence: 69%
“…Third, all sleeps for the Australians were compared with all sleeps for the Bolivians to examine potential differences between sea-level natives and high-altitude natives at near sea level and at high altitude. Finally, given that there is some evidence that competition exercise impairs the subsequent sleep of elite athletes,24 an additional set of analyses was conducted to compare sleep on match days with sleep on non-match days for each team separately. These additional analyses were conducted with a subset of the sample that included only athletes who played at least 45 min in a day match and at least 45 min in a night match (ie, 10 Australian players and 9 Bolivian players).…”
Section: Methodsmentioning
confidence: 99%
“…Using sleep diary assessments, Fullagar et al [59] also reported a decrease in sleep ‘restfulness’ in elite football players following a night competition, compared with day matches and training days. In the only study assessing PSG-measured sleep structure, Netzer et al [61] reported a significant increase in stage 3 sleep following competition (compared with rest days) and a significantly increased REM sleep onset latency. However, no changes in sleep onset latency or sleep efficiency were reported.…”
Section: Resultsmentioning
confidence: 99%
“…For example, travel (Richmond et al, 2004), competition (Driver et al, 1994;Netzer et al, 2001) and intense training (Taylor et al, 1997) are all known to disrupt or reduce the amount and/or quality of sleep obtained by elite athletes. However, the timing of an athlete's training schedule may also be of importance.…”
Section: Impact Of Training Schedules On Athletes' Sleepmentioning
confidence: 99%